Pachydermoperiostosis Mimicking Acromegaly: a Rare Case Report in Sardjito General Hospital Yogyakarta Indonesia - Saiful Anam; Hemi Sinorita (Journal of World Science, 2024)
Pachydermoperiostosis is a genetic disorder characterized by pachydermia and periostosis. The clinical and radiological features of pachydermoperiostosis are similar to acromegaly. The Prevalence of pachydermoperiostosis is estimated 0.16%. The ratio of male-to-female incidence is 7 to 1. We report a man 26 years old with complaints of pain and swelling in the wrist joints, fingers, knee joints and ankle joints bilaterally; seborrheic dermatitis, eyelid ptosis, and thickening of facial skin, which has been progressive since he was 17 years old. Manus, genu and pedis x-ray results showed a features of mixed connective tissue disease. Magnetic resonance imaging result of the pituitary gland with contrast  was normal. Laboratory results for growth hormone (GH) and insulin growth factor-1 (IGF-1) were normal. Histopathology results of the facial skin biopsy showed grade 1 pachydermia in pachydermoperiostosis. In conclusion, the appearance of pachydermia on skin biopsy, with normal  growth hormone and insulin growth factor-1 results can differentiate pachydermoperiostosis from acromegaly.